2015
DOI: 10.1080/11356405.2015.1072360
|View full text |Cite
|
Sign up to set email alerts
|

The academic writing process in Spanish universities: perceptions of students and faculty / El proceso de escritura académica en la universidad española: percepciones de estudiantes y profesores

Abstract: This paper is intended as an exploration of university faculty and students' perceptions of a number of dimensions involved in the written composition of academic texts. We analysed the responses to scale 3 in the European Writing Survey (EUWRIT) (in its Spanish version: Encuesta Europea sobre la Escritura Académica, EEEA) by a group of social science and humanities students (n = 1,030) and faculty (n = 230) from nine Spanish universities. We then examined the similarities and differences in their perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
4
0
9
Order By: Relevance
“…Based on the responses to these questions, we can draw a general conclusion that the results found in the distance-learning modality are quite similar to those found in the face-to-face modality, both in how writing practices are described and in some of the differences in faculty's and students' perceptions (Marín et al, 2015). Thus, for example, the data from this study reveal that the text product is valued more than the intellectual process of writing (Carlino, 2013), as activities oriented at the process were done quite seldom (Castelló & Mateos, 2015), given that a significant proportion of students write a draft before beginning to write a text only rarely or sometimes, and they state that they always receive only a grade for their written work.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on the responses to these questions, we can draw a general conclusion that the results found in the distance-learning modality are quite similar to those found in the face-to-face modality, both in how writing practices are described and in some of the differences in faculty's and students' perceptions (Marín et al, 2015). Thus, for example, the data from this study reveal that the text product is valued more than the intellectual process of writing (Carlino, 2013), as activities oriented at the process were done quite seldom (Castelló & Mateos, 2015), given that a significant proportion of students write a draft before beginning to write a text only rarely or sometimes, and they state that they always receive only a grade for their written work.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies conducted in Spain like Castelló and Mateos (2015), Castells et al (2015), Corcelles et al (2015) and Marín et al (2015) found that epistemic writing tasks in university education are scarcely or never assigned. Thus, in the opinion of Castelló and Mateos (2015), their absence is one of the main findings of studies framed within these two approaches (WAC and WID) which have examined the status of academic writing in Spain and the Latin American countries.…”
Section: Writing As a Tool For Learning At Universitymentioning
confidence: 99%
“…Idazketa akademikoa, hortaz, jarduera konplexua da, konpetentzia anitz menderatzea eskatzen duena. Horien artean, hurrengoak ditu bere baitan: testuen ekoizpenean agertzen diren mekanismo diskurtsiboen kudeaketa, diziplinaren ezagutza eta diziplina horretara lotuta dauden genero diskurtsiboen ezagutza, arlo horretan ekoiztu diren testuen ulermena, hizkuntzaren erabilera zuzena eta egokia, idazteak eskatzen dituen erregulazio-prozesuen koordinazioa eta diskurtsoaren inguruko komunitatearen eskaera nahiz itxaropenei erantzuna ematea (Marín, López eta Roca de Larios, 2015). Hori dela eta, unibertsitateko lehen ikasturtetik, ikasleek hainbat genero diskurtsibotako idatzizko testuak ekoitzi behar dituzte: idatzizko azterketak, txostenak, erreseinak, etab.…”
Section: Alfabetatze Akademikoaunclassified
“…Es decir, los universitarios deben aprender a comunicarse como los miembros de la comunidad universitaria de la que son parte al igual que como los miembros de las comunidades discursivas profesionales de las que pretenden formar parte en su futuro (Carlino, 2013). Asimismo, han de ser conscientes de su propio proceso de escritura, de los recursos de los que disponen y de los diferentes géneros y modos de escribir que les serán necesarios (Camps, 2011;Carlino, 2003;Lacon y Ortega, 2008;Marín, López, & Roca-De-Larios, 2015). El segundo objetivo de la alfabetización académica es ayudar a los estudiantes a apropiarse del conocimiento producido por ellos durante el proceso de escritura.…”
Section: La Alfabetización Académica En La Enseñanza Superiorunclassified